Strategi Pengawasan Internal Penyaluran Pupuk Subsidi Dalam Rangka Transparansi Program E-Rdkk Di Kelurahan Tangkahan Medan Labuhan - Nirwana Nirwana; Jehan Ridho Izharsyah (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
Internal supervision is carried out by supervisory officers who come from special supervisory institutions which are formed internally by the Government or Executive agencies. The Nusajadi Farmers Group collaborates with the Village Unit Cooperative in Tangkahan Village with the E-rdkk program to record the amount of agricultural land owned by each farmer. In the distribution of subsidized fertilizers to each farmer through farmer groups in their respective neighborhoods, some of which have been recorded through government programs that are related to the Medan City Agriculture Service. The formulation of the problem in this research is the strategy of internal supervision of subsidized fertilizer distribution in the context of the transparency of the E-rdkk Program in Tangkahan Village, Medan Labuhan. The purpose of this study was to find out how the Internal Supervision Strategy for Subsidized Fertilizer Distribution in the Context of Transparency of the E-RDKK Program in Tangkahan Village, Medan Labuhan. The type of research used in this study is a qualitative approach with qualitative analysis. The data collection technique or method that the author uses in this research is the Interview Technique and In-depth Interview (in-depth interview). The data analysis technique used in this research is inductive data analysis. Inductive data analysis is drawing conclusions that depart from specific facts, to then draw general conclusions. So the authors conclude that the Internal Supervision Strategy for Subsidized Fertilizer Distribution in the Context of Transparency of the E-rdkk Program in Tangkahan Village, Medan Labuhan has been achieved but has not been implemented effectively.